The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/adma.201202211
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Polypyrrole Nanoparticles with High Photothermal Conversion Efficiency for Photothermal Ablation of Cancer Cells

Abstract: Uniform polypyrrole (PPy) nanoparticles are fabricated from a facile one-step aqueous dispersion polymerization. Owing to their high photothermal conversion efficiency and photostability compared with the well-known Au nanorods, as well as their good colloidal stability and biocompatibility, the resulting PPy nanoparticles can used as a novel promising photothermal ablation coupling agent for targeted treatment of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
502
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 698 publications
(520 citation statements)
references
References 50 publications
8
502
0
1
Order By: Relevance
“…Light has a higher penetration depth in the NIR optical window between 700 and 900 nm, where human tissue has minimal absorption, scattering, and fluorescence. 8 A vast majority of the research in this field has focused on the use of gold nanoparticles (GNPs), including gold nanorods (GNRs) 9 and gold nanoshells (GNSs), 10,11 as well as the use of carbon-based materials, including conductive polymers, [12][13][14][15] graphene oxide, 16 and single-and multiwalled carbon nanotubes 17,18 as PTT agents. While the potential of GNPs has been demonstrated in several instances and their development has reached the level of phase 1 clinical trials, the effectiveness and safety of carbon-based PTT agents have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Light has a higher penetration depth in the NIR optical window between 700 and 900 nm, where human tissue has minimal absorption, scattering, and fluorescence. 8 A vast majority of the research in this field has focused on the use of gold nanoparticles (GNPs), including gold nanorods (GNRs) 9 and gold nanoshells (GNSs), 10,11 as well as the use of carbon-based materials, including conductive polymers, [12][13][14][15] graphene oxide, 16 and single-and multiwalled carbon nanotubes 17,18 as PTT agents. While the potential of GNPs has been demonstrated in several instances and their development has reached the level of phase 1 clinical trials, the effectiveness and safety of carbon-based PTT agents have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanomaterials such as nanorods [24], nanoshells [25], nanostars [26] and nanocages [27,28] are one of the mostly investigated agents due to their easy accessibility. Yet, recent results indicated that these kinds of photothermal agents suffer from poor photostability under continuous irradiation of NIR light [29,30]. Such issue has driven researchers to explore novel types of photothermal agents.…”
Section: Introductionmentioning
confidence: 99%
“…This could induce a controlled and sustained release in the appropriate environment. The triggered release of a drug in an appropriate location upon external stimuli such as changes of pH or redox environment would qualify the ppy-chit nanospheres as smart materials 11 .…”
Section: Introductionmentioning
confidence: 99%